Efficient aqueous dye-sensitized solar cell electrolytes based on a TEMPO/TEMPO+ redox couple1. Issue 34 (15th April 2015) - Yang, Wenxing; Söderberg, Magnus; Eriksson, Anna I. K.; Boschloo, Gerrit
<x xml:space="preserve">Abstract</x> Aqueous electrolyte-based dye-sensitized solar cells (DSSCs) have recently emerged and shown to be promising eco-friendly photovoltaic devices.